Implementasi Pembelajaran Internet of Things (IoT) Berbasis Project-Based Learning pada Siswa Kelas 12 MA Nurul Ummah Yogyakarta - Hanif Amarudin; Naufal Hafizh Mufafaq; Bambang Sugiantoro (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2026)
The digital divide and limited infrastructure at the secondary education level often hinder the mastery of Internet of Things (IoT) technology, which is crucial for students' career readiness. This community service program aims to improve 12th-grade students' understanding of basic IoT concepts and technical skills at MA Nurul Ummah Yogyakarta, to facilitate their transition to college or work. The implementation method applied a Project-Based Learning (PjBL) approach assisted by the Tinkercad simulator, involving 71 students in 36 working groups. Participants were given theoretical training followed by a practical, simple project design, including traffic lights, light sensors, temperature sensors, and running text. The results of the activity showed a project completion success rate of 70.59%, with the temperature sensor project achieving the highest success rate (100%). Cognitively, the post-test evaluation showed a significant increase, with 69.23% of students achieving a “Very Good” rating (score of 100), despite the majority having limited prior knowledge. It was concluded that simulation-based IoT education proved to be effective and efficient in improving students' digital literacy and problem-solving skills, although challenges in programming logic still require further study.